A Comparison of Different Gas Turbine Engines Ground Vortex Flows - Barata, Jorge M M (2012)
A computational method was used to predict and compare the ground vortices forming between the ground and a 1/1th scale model intake of different gas turbine engines. Calculations have been performed for the case of an irrotational crossflow mode of formation. Two different kinds of vortices appear around the intake: an inlet vortex and a trailing vortex. Away from the inlet plane other types of complex vortical structures were also identified. The computational method was found to describe all the main features of the flow for full scale geometry.